Wilderness tales : forty stories of the North American wild - Fuss, Diana, 1960-; Irving, Washington, 1783-1859; Hawthorne, Nathaniel, 1804-1864; Douglass, Frederick, 1818-1895; Young, Nathan B., 1894-1993; Cooper, James Fenimore, 1789-1851; Spofford, Harriet Elizabeth Prescott, 1835-1921; Bierce, Ambrose, 1842-1914?; Groff, Lauren; London, Jack, 1876-1916; Roberts, Charles G. D., Sir, 1860-1943 (Alfred A. Knopf, 2023)
"An anthology of short stories about the North American wilderness"--